Motivation conditions in a foreign language reading comprehension course offering both a web-based modality and a face-to-face modality (2014)
Motivation plays an important in role in education. Based on the ten macro-strategies proposed by Dörnyei and Csizér (1998), this article analyzes the motivation conditions in a foreign language reading comprehension course using both a web-based modality and a face-to-face modality. A case study was implemented as the primary research method, and five instruments were used to gather data: observations, a teacher’s diary, focus groups, questionnaires, and in-depth interviews. The use of teaching aids, mastery gains in reading, proper presentation of tasks, and lack of humor were among the similarities found in the courses. In contrast, constant motivation, technical support, interactions among students, anxiety, and a high number of exercises constituted some of the differences between the modalities.La motivación juega un papel importante en la educación. Basados en las diez macro-estrategias propuestas por Dörnyei y Csizér, este artículo analiza las condiciones de motivación en un curso de comprensión de lectura en lengua extranjera ofrecido en las modalidades a distancia en la web y presencial. Se implementó un estudio de caso como método de investigación y se utilizaron cinco instrumentos para recoger la información: observaciones, diario del profesor, grupos focales, cuestionarios y entrevistas a profundidad. El uso de ayudas de enseñanza, la mejora en la lectura, la presentación adecuada de las actividades y la carencia de humor son algunas de las similitudes encontradas en estos dos cursos. En contraste, una motivación más individual y positiva, la interacción entre los estudiantes, la ansiedad y la cantidad de ejercicios se constituyen en algunas diferencias entre las dos modalidades.